Optimizing location and size of capacitors for power loss reduction in radial distribution networks - Thuan Thanh Nguyen; Phan Nguyen Vinh; Hung Duc Nguyen; Ly Huu Pham; Thang Trung Nguyen (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2021)
Power radial distribution systems are increasingly more and more important in transmitting the electric energy from power plants to customers. However, total loss in lines are very high. This issue can be solved by allocating capacitor banks. Determining the suitable allocation and optimal sizing of capacitor banks needs an efficient approach. In this study, the diffusion and update techniques-based algorithm (DUTA) is proposed for such reason. The efficiency of DUTA is inspected on two distribution systems consisting of 15-bus and 33-bus systems with different study cases. The solutions attained by DUTA are competed with recently published methods. As a consequence, the method is more effective than the other methods in terms of the quality of solution.